NATIONAL FINANCIAL SYSTEM ANALYSIS IN TERMS OF THE COMPLEX SYSTEMS THEORY (International Journal of Innovative Technologies in Economy, 2020)
The recession caused by the pandemic and the vulnerabilities faced by the entire international monetary system and the national financial systems requires a particular approach to analyzing the current situation and the design of new developments. Based on these arguments, we set out to investigate national financial systems from the perspective of complex systems theory.Following the research, we concluded that understanding the nature and characteristics of the manifestation of synergistic effects allows organizing the financial system's management at a new quality level, based on the concepts of discretion and stability of development trajectories of the world economy.